Opening address at the Symposium on Saami religion arranged by the Donner Institute 16-18 August 1984 - Carl-Martin Edsman (Scripta Instituti Donneriani Aboensis, 1987)
This paper is based on the words of welcome to the symposium on Saami Religion.